2012
DOI: 10.1186/1471-244x-12-126
|View full text |Cite
|
Sign up to set email alerts
|

Mu opioid receptor availability in people with psychiatric disorders who died by suicide: a case control study

Abstract: BackgroundMu opioid receptors have previously been shown to be altered in people with affective disorders who died as a result of suicide. We wished to determine whether these changes were more widespread and independent of psychiatric diagnoses.MethodsMu receptor levels were determined using [3 H]DAMGO binding in BA24 from 51 control subjects; 38 people with schizophrenia (12 suicides); 20 people with major depressive disorder (15 suicides); 13 people with bipolar disorder (5 suicides) and 9 people who had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
(60 reference statements)
2
19
1
1
Order By: Relevance
“…[ 11 C]-carfentanil PET studies have also demonstrated higher μOR availability among recently abstinent alcohol-dependent individuals than controls (Heinz et al, 2005; Weerts et al, 2011). The studies reviewed here also excluded individuals with psychiatric problems including depressive, psychotic, or anxiety disorders, which have been found to affect μOR availability (Naber et al, 1981; Gross-Isseroff et al, 1990; Kennedy et al, 2006; Prossin et al, 2010; Scarr et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…[ 11 C]-carfentanil PET studies have also demonstrated higher μOR availability among recently abstinent alcohol-dependent individuals than controls (Heinz et al, 2005; Weerts et al, 2011). The studies reviewed here also excluded individuals with psychiatric problems including depressive, psychotic, or anxiety disorders, which have been found to affect μOR availability (Naber et al, 1981; Gross-Isseroff et al, 1990; Kennedy et al, 2006; Prossin et al, 2010; Scarr et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Post‐mortem measurements of μ receptor binding in suicide victims have yielded mixed results, with some studies finding higher binding (Gross‐Isseroff et al, ; Gabilondo et al, ), some lower binding (Scarr et al, ) and some no difference at all (Zalsman et al, ). There are only two in vivo studies of μ receptor availability in depression.…”
Section: Sadness and Depressionmentioning
confidence: 99%
“…Previous post-mortem and imaging studies suggested that adaptations at the level of mu (Gabilondo et al, 1995; Gross-Isseroff et al, 1990; Kennedy et al, 2006; Scarr et al, 2012) or kappa (Hurd, 2002; Pietrzak et al, 2014) opioid receptors signaling may contribute to suicide pathophysiology. Extending on these findings, the present study shows that suicide completers exhibit decreased levels of N/OFQ mRNA in the dACC, compared to non-suicidal control subjects.…”
Section: Discussionmentioning
confidence: 99%